The ingenious hidalgo Don Quixote de la Mancha - Cervantes Saavedra, Miguel de, 1547-1616 (Penguin classics, 2003)
The story of the adventurous knight-errant and his squire Sancho Panzo, who set out to right the wrongs of the world.